Cancer Cell Mechanics in Chemoresistance and Chemotherapeutic Drug Exposure - Smith, Rochelle (Department of Human Biology, 2020)
Cancer remains a problem worldwide as one of the leading causes of morbidity and mortality. Many cancer patients experience recurrence and ultimately death due to treatment failure or the development of chemoresistance. The concept of chemoresistance however is complex, recent studies have highlighted that cellular structure and extra-cellular composition, mechanics and structure play a role in the development of chemoresistance. The mechanical properties of cells impact their architecture, migration patterns, intracellular trafficking and many other cellular functions. Studies have also revealed that cellular mechanical properties are modified during cancer progression. We investigated these mechanical properties and changes to them by using a malignant melanoma cell line (WM1158) and a chemoresistant malignant melanoma cell line (SK-MEL29). Malignant melanoma was the cell line of choice as it is one of the most prominent types of cancer known to develop chemoresistance. The aim of this study was to identify the effects of chemotherapeutic drug exposure on the mechanical properties and cytoskeletal composition of drug sensitive and drug resistant malignant melanoma cells. To achieve this, a combination of Multiple particle tracking microrheology (MPTM), quantitative RT-PCR and Western blotting techniques were utilised to demonstrate changes in cytoskeletal elements that are responsible for cellular mechanics. MPTM was developed as an approach to map intracellular mechanical properties of living cells and track the intracellular particles by Brownian motion to establish a viscoelastic model and compare it with the power-law approach. A quantification of the MPTM allowed capturing of the cell stiffness using the mean squared displacement (MSD) of cell under different conditions. The cytoskeletal elements actin and β-tubulin were analysed in qRT-PCR and Western blot as they form the key elements governing a cell’s mechanical stability and response to mechanical stimuli. The findings from this study revealed cell stiffness decreases as cancer progress, thereby cells become stiffer. The same pattern was evident for chemoresistant malignant cells and revealed that they had a loss of elasticity in comparison to their counter non-resistant malignant cells. With regards to protein levels and mRNA expression, the chemotherapeutic drug affected the cytoskeleton causing cells to undergo morphological changes which, however, was not seen in chemoresistant cells. The results from this study indicated that measuring mechanical properties of cells provides an efficient marker for cancer diagnosis and deeper understanding of cancer mechanobiology.